An inexact l2-norm penalty method for cardinality constrained portfolio optimization. Issue 3 (3rd July 2019) - Jiang, Tao; Wang, Shuo; Zhang, Ruochen; Qin, Lang; Wu, Jinglian; Wang, Delin; Ahipasaoglu, Selin D.
Abstract: We analyze and solve a single-period portfolio optimization problem with non-convex constraints, which address practical concerns of investment such as the active share weights of sectors and the number of stocks held in a portfolio. We reformulate the problem to simplify the computation and propose an inexact l 2 -norm penalty method to solve the problem.